Implementasi Model PBL Di Kelas V SDN Teluk Tiram 6 Untuk Meningkatkan Keterampilan Kolaborasi - Linda Rosydah (BADA'A: Jurnal Ilmiah Pendidikan Dasar, 2025)
This research used Classroom Action Research which was conducted in 3 meetings. The subjects of this study were class V students of Teluk Tiram 6 State Elementary School, class V, totalling 24 people. Qualitative data collection was obtained through observation of educator activities, learner activities and collaboration. As well as quantitative data includes the classical percentage collaboration obtained from group and individual tests. The results showed that the teacher's activity at meeting I obtained "Very Good" criteria with a score of 19 increasing to a score of 20. The activity of students at meeting I was 63%. at meeting III was 100%. Collaboration skills at meeting I obtained 54%, increased at meeting III by 88%. Learning outcomes in cognitive, affective and psychomotor aspects at the first meeting of students who were "Completed" by 71%, increasing at meeting III to 100%.